The level of trust of santri in choosing the shelter services of the University of ‘Aisyiyah Yogyakarta - Kharisah Diniyah; Sri Lestari (Universitas 'Aisyiyah Yogyakarta, 2022)
The number of people affected by Covid 19 in the world continues to increase every day. Based on the Worldometers page, as of September 23, 2020, the total number of confirmed Covid-19 cases in the world is 31,749,508 (31.7 million) issues. The recovery rates have also increased, but some people at high risk can cause serious health problems (Task Force on COVID-19). Emotional and mental disorders can occur due to the Covid-19 Pandemic, especially in people who have to isolate/quarantined. Such conditions cause the need to provide shelters for activities for people undergoing self-isolation so that anxiety can be controlled and immunity can increase. The study aims to determine the level of trust of santri in choosing the 'Aisyiyah Yogyakarta University (Unisa) Shelter. This research is a quantitative analytic survey study with a single variable, namely the trust of covid 19 students, involving 30 respondents. Accidentally involving, 30 respondents determined the criteria by filling out a standardized satisfaction questionnaire using descriptive analysis. The results showed that 100% of respondents highly trust the Unisa shelter as a place for self-isolation. The trust is based on three dimensions where the dimensions of ability and benevolence are at a high level of trust, while the integrity dimension is at a moderate level of trust. In the integrity dimension, where the level of trust is moderate, skill performance still needs to be improved.